An in-situ infrared temperature-measurement method with back focusing on surface for creep-feed grinding. (December 2016) - Liu, Dehao; Wang, Gang; Nie, Zhenguo; Rong, Yiming (Kevin)
Abstract: In creep-feed grinding research, it is vital to measure surface temperature of workpiece in order to optimize process parameters, prevent potential thermal damage, improve the surface integrity of workpiece and provide reference for modelling of grinding. Various measurement techniques for grinding temperature have been developed by using thermocouples and infrared radiation techniques. However, some inevitable problems still exist with slow response, strong noise interference and high sensibility to coolants. In order to obtain precise and reliable temperature of workpiece surface during grinding, an in-situ infrared technique is designed by focusing on the back surface of workpiece. With the help of a two-dimensional sliding table, the focus of infrared thermometer can be adjusted to the small hole in the workpiece to measure grinding temperature accurately. This method can avoid the high-frequency signal interruption of mechanical vibration and electrical noises, since the measurement is contactless and has signal shielding. The procedures to set up the measurement facility and measure grinding temperature are described in this paper. This paper also includes the analysis of measurement results of grinding temperature. Compared with other measurement techniques, this method is not affected by mechanical vibration and grinding fluids. By using infrared technology, this method can measure accurate grinding temperature with a fast response.